Updating on the fungal composition in Sardinian sheep's milk by culture-independent methods. Issue 2 (May 2014) - Panelli, Simona; Brambati, Eva; Bonacina, Cesare; Feligini, Maria
<x content-type="archive" xml:space="preserve">Abstract</x> This work applies culture-independent methods for the characterization of fungal populations (yeasts and moulds) naturally occurring in Sardinian ewe's milk sampled in the Italian areas with the largest dairy production (Sardinia and Lazio regions). Sequences of the D1/D2 variable domains at the 5′ end of the 26S rRNA gene were obtained by amplification of DNA directly isolated from milk, and this allowed identification of a total of 6 genera and 15 species of fungi. Among the 6 identified genera Geotrichum spp., Candida spp., Phaeosphaeriopsis spp., Pestalotiopsis spp. and Cladosporium spp. belong to the phylum of Ascomycota, while Cryptococcus spp. is part of the phylum of Basidiomycota. In particular, two genera (Pestalotiopsis and Phaeosphaeriopsis) and two species (Plectosphaerella cucumerina and Pryceomyces carsonii) have never been reported in dairy ecosystems before. Results provide evidence that several moulds and yeasts, previously described only in ovine cheeses, are transferred directly from raw milk. The knowledge of fungal consortia inhabiting sheep raw milk is a particularly relevant issue because several species are directly involved in cheese making and ripening, determining the typical aroma. On the other hand, spoilage yeasts and moulds are involved in anomalous fermentation of cheese and may be responsible for considerable economic losses and serious risks for consumers' health.